Forensic Audit Bibliometric Analysis: World Scientific Publications In 2019-2024 - Razy Ulul Azima; Muhammad Yusuf (Economics and Business Faculty UNUSIA, 2025)
Penelitian ini bertujuan untuk mengetahui perkembangan publikasi ilmiah terkait forensic auditing dengan menggunakan analisis bibliometrik. Peneliti mengumpulkan data dari basis data Scopus dengan menggunakan kata kunci forensic audit pada periode 2019–2024. Hasil penelitian menunjukkan bahwa perkembangan riset mengenai forensic audit dari tahun 2019 hingga 2024 terus mengalami peningkatan, dengan jumlah publikasi terbanyak terdapat pada ACM International Conference Proceeding Series dan Journal of Financial Crime. Kata kunci: Forensic Audit, Fraud, Bibliometrik. Abstract This research aims to determine the development of scientific publications related to forensic auditing using bibliometric analysis. Researchers collected data from the Scopus database using the keywords forensic audit in the 2019-2024 period. The results of the research show that the development of forensic audit research from 2019-2024 continues to increase with the most publications in the ACM International Conference Proceeding Series and Journal of Financial Crime Keywords: Forensic Audit, Fraud, Bibliometric